More Maternal Vascular Malperfusion and Chorioamnionitis in Placentas After Expectant Management vs. Immediate Delivery in Fetal Growth Restriction at (Near) Term: A Further Analysis of the DIGITAT Trial - Feenstra, Marjon E.; Schoots, Mirthe H.; Plösch, Torsten; Prins, Jelmer R.; Scherjon, Sicco A.; Timmer, Albertus; van Goor, Harry; Gordijn, Sanne J. (Frontiers in Endocrinology, 2019)
Abstract Objective Management of late fetal growth restriction (FGR) is limited to adequate fetal monitoring and optimal timing of delivery. The Disproportionate Intrauterine Growth Intervention Trial At Term (DIGITAT) trial compared induction of labor with expectant management in pregnancies at (near) term complicated by suspected FGR. Findings of the DIGITAT trial were that expectant monitoring prolonged pregnancy for 10 days and increased birthweight with only 130 grams. This resulted in more infants born below the 2.3rd percentile compared to induction of labor, respectively 12,5% in induction of labor and 30,6% in expectant monitoring group. The main placental lesions associated with FGR are maternal vascular malperfusion, fetal vascular malperfusion, and villitis of unknown etiology. We investigated whether placentas of pregnancies complicated with FGR in the expectant monitoring group reveal more and more severe pathology due to pregnancy prolongation. Material and methods The DIGITAT trial was a multicenter, randomized controlled trial with suspected FGR beyond 36+0 weeks. We now analyzed all available cases (n=191) for placental pathology. The macroscopic details were collected and histological slides were recorded and classified by a single perinatal pathologist, blinded for pregnancy details and outcome. The different placental lesions were scored based on the latest international criteria for placental lesions as defined in the Amsterdam Placental Workshop Group Consensus Statement. Results The presence of maternal vascular malperfusion and chorioamnionitis were higher in the expectant management group (p<0.05 and p<0.01 respectively). No differences in placental weight and maturation of the placenta between the induction of labor and the expectant management group were seen. Fetal vascular malperfusion, villitis of unknown etiology and nucleated red blood cell count did not differ between the groups. Conclusion Expectant management of late FGR is associated with increased maternal vascular malperfusion and chorioamnionitis. This may have implications for fetal and neonatal outcome, such as programming in the developing child influencing health outcomes later in life.